Komunikasi Interpersonal dalam Pengalaman Kehilangan Figur Ayah - Agnes Rosandi; Sinta Paramita (Kiwari, 2026)
This research explores the role of interpersonal communication in early adults who experienced fatherlessness. The study focuses on how the absence of a father figure affects individual emotional formation, communication patterns, and social relationships. Using the constructivist paradigm and qualitative descriptive method, this research involved informants who experienced the absence of a father figure during their growth period. Data were collected through in-depth interviews and analyzed thematically. The results show that fatherlessness impacts the ability to express emotions, build trust, and form meaningful relationships. The findings also reveal coping mechanisms such as self-reliance, self-talk, and selective communication as adaptive responses. In conclusion, interpersonal communication plays a vital role as a medium for self-expression, emotional regulation, and social adaptation among early adults with fatherless experiences. Penelitian ini membahas peran komunikasi interpersonal pada individu dewasa awal yang mengalami kehilangan figur ayah. Fokus penelitian ini adalah memahami bagaimana ketiadaan figur ayah mempengaruhi pembentukan emosional, pola komunikasi, dan hubungan sosial individu. Penelitian menggunakan paradigma konstruktivis dengan metode deskriptif kualitatif. Subjek penelitian adalah informan yang kehilangan figur ayah sejak masa pertumbuhan. Pengumpulan data dilakukan melalui wawancara mendalam dan dianalisis menggunakan pendekatan tematik. Hasil penelitian menunjukkan bahwa kehilangan figur ayah berpengaruh terhadap kemampuan mengekspresikan emosi, membangun kepercayaan, serta menjalin hubungan interpersonal yang bermakna. Selain itu, ditemukan mekanisme coping seperti kemandirian, self-talk, dan komunikasi selektif sebagai bentuk adaptasi psikologis. Kesimpulannya, komunikasi interpersonal memiliki peran penting sebagai sarana ekspresi diri, pengaturan emosi, dan penyesuaian sosial bagi dewasa awal yang kehilangan figur ayah.